Methods for Enhanced Fluorescence Detection of Proteins by using Entrapped Gold Nanoparticles in Membranes. Issue 3 (25th March 2022) - Momenbeitollahi, Nikan; van der Zalm, Joshua; Chen, Aicheng; Li, Huiyan
Abstract: Measuring protein levels from biofluids can provide important insight into human health and disease during various physiological and pathological conditions. In many situations, sensitive methods are required for protein quantification because at the early stages of many diseases, proteins in biofluids are present at very low concentrations. Here, a new and simple method is presented in the form of Basic and Alternative Protocols for an immunoassay performed on a nitrocellulose membrane, followed by the addition of gold nanoparticles prior to measuring fluorescence with a microscope. The assay protocol was optimized to achieve 3D metal‐enhanced fluorescence (MEF) with increased antibody‐binding capacity and enhanced fluorescence signals, improving assay sensitivity. Using different concentrations of spiked fluorescently labeled IgGs in pooled normal human plasma, a lower detection limit of 29 ng/ml was achieved. This limit of detection was found to be a thousand‐fold lower than the conventional 2D assay and one order of magnitude lower than when the assay was performed on a 3D membrane without MEF. This method provides an easy way to improve immunoassay sensitivity, and it can be simply transferred to other labs. It also can extend to fluorescence detection of other analytes beyond proteins. © 2022 Wiley Periodicals LLC. Basic Protocol : Assay in nitrocellulose membrane with entrapped AuNPs using commercially available AuNPs Alternative Protocol : Assay in nitrocellulose membrane with entrapped AuNPs using lab‐made AuNPs